FY 2019 Colombia Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2020)
The Country Opinion Survey in Colombia assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Colombia perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Colombia on 1) their views regarding thegeneral environment in Colombia; 2) their overall attitudes toward the WBG in Colombia; 3)overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Colombia; and 4) their perceptions of the WBG’sfuture role in Colombia.